Pelatihan Meningkatkan Kualitas Modul Ajar Dengan Aplikasi Canva Pada Kurikulum Merdeka Bagi Guru-Guru SMK IT Al Hidayah Pasaman Barat - Novita, Rini; Alfiriani, Adlia; Irsyadunas, Irsyadunas; Nurdin, Bernediv (JURNAL PKM IKA BINA EN PABOLO, 2024)
Training to Improve the Quality of Teaching Modules with the Canva Application in the Independent Curriculum for Teachers at Al Hidayah IT Vocational School, West Pasaman. This research aims to improve the quality of teaching modules through training on the use of the Canva application in the Merdeka curriculum for teachers at Al Hidayah IT Vocational School, West Pasaman. The Merdeka Curriculum is a learning approach that prioritizes flexibility, creativity and student skill development. In this context, teaching modules become a very important tool to support an effective learning process. The research method used was the implementation of training for Al Hidayah IT Vocational School teachers in West Pasaman regarding the use of the Canva application in creating teaching modules. Training is carried out through interactive sessions, step-by-step guides, and case studies to understand the concept of the application. Teachers are also given the opportunity to try directly creating teaching modules using Canva in a simulative learning environment. It is hoped that the results of this activity will enable the Al Hidayah IT Vocational School teachers in West Pasaman to develop more interesting and informative teaching modules using the Canva application. They can take advantage of Canva's various features, such as attractive template designs, adding graphic elements, and creative text arrangement. This activity was carried out in relation to the demands of higher education through Community Service (PkM) activities. One of the alternative solutions offered by the PkM team is to provide training in creating teaching modules produced through Canva that show increased visual quality and diversity of content, which in turn increases students' interest and understanding of learning material and will be published in online media and service journals.